Cutaneous healing after topical application of nebacetin and gingilone to infected wounds. Clinical and histological study in rats - Perri de Carvalho, Paulo Sérgio [UNESP]; de Oliveira, G. M. (Revista De Odontologia Da Unesp / Universidade Estadual Paulista (unesp), 1990)
It was performed a study to examine the cutaneous cicatrization of infected wound of skin after daily topic application of Nebacetin and Gingilone. Following clinical observations the animals were sacrificed after 4, 10 and 17 post-operative days. The pieces were treated, analyzed, in an optical microscope. The topic application of Nebacetin showed to be more efficient in the epithelial reparation comparatively to the Gingilone and control group.